PENGARUH STRATEGI BERHITUNG (DIFFERENT STRATEGIES) TERHADAP HASIL BELAJAR MATEMATIKA SISWA PADA OPERASI BILANGAN BULAT DI KELAS III SD NEGERI NO 114349 SIDUA-DUA - Nurdalilah Nurdalilah (State Islamic University of North Sumatra, 2018)
This study aims to find out (1) students 'learning outcomes of mathematics taught with different strategies, (2) students' mathematics learning outcomes taught by traditional algorithms, (3) Are there different effects of counting strategies on results learn mathematics students on integer operation material. This research is a quantitative research with kind of quasi-experimental research. The population in this study were all third grade students of Public Elementary School 114349. The sample in this study was class III-1 as an experimental class with a total of 30 students and class III-2 as a control class with a total of 30 students. The findings in this study indicate that classes taught by using different strategies have an average value of 31.970 and the classes taught by algorithm have an average value of 28,5758. The results of hypothesis testing show that t count> t table is 2.925> 2.0018 with the conclusion that students' mathematics learning outcomes are taught with different strategies better than those taught with traditional algorithms on integer operation material in Public Elementary School No. 114349 Academic Year 2016/2017